2020
DOI: 10.1002/pc.25873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro‐sized marble dust on mechanical and thermo‐mechanical properties of needle‐punched nonwoven jute fiber reinforced polymer composites

Abstract: This work explores effectiveness of marble dust as a filler in needle‐punch nonwoven jute fiber reinforced polymer composites, prepared through vacuum‐assisted resin transfer molding process. Four different particulate filled composites are fabricated by varying the filler percentage from 0 to 24 wt% at an interval of 8 wt% marble dust under the controlled environment. The mechanical characterizations such as flexural strength, interlaminar shear strength, compressive strength, and impact strength enhanced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The decreased interparticle spacing using stiffer hard particles (marble dust in this case) with increased bagasse fiber loading resulting in a compact structure which absorbs more energy before failure. [ 34 ] Similar results for increased impact energy were reported for granite powder/marble dust/jute fiber reinforced epoxy hybrid composites by Pawar et al [ 30 ] and Sharma et al [ 31 ]…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The decreased interparticle spacing using stiffer hard particles (marble dust in this case) with increased bagasse fiber loading resulting in a compact structure which absorbs more energy before failure. [ 34 ] Similar results for increased impact energy were reported for granite powder/marble dust/jute fiber reinforced epoxy hybrid composites by Pawar et al [ 30 ] and Sharma et al [ 31 ]…”
Section: Resultssupporting
confidence: 73%
“…[ 36 ] Also, increased waste bagasse fiber loading with hard marble dust particles resulted in a more packed/compact structure, which resists the crack formation/growth and, consequently, brings about the composites expanded mechanical properties. Pawar et al [ 30 ] and Sharma et al [ 31 ] revealed similar improvement in flexural strength with granite powder/marble dust filler with jute fiber reinforced epoxy composites.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The poor strength of the composites in comparison to PHPC0 can be due to poor particle-matrix debonding and easy breakage that may have occurred due to improper formation of strong bonds between the matrix and the PS particles. Similar results were reported with the use of micro-sized marble dust [30]. The higher flexural strength for PHPC90 samples was observed when compared with the other -article sizes of PSP.…”
Section: Flexural Propertiessupporting
confidence: 86%
“…Similar trends for the void fraction with increased particulate filler were reported in the literature. [18,37] It may be seen that the incorporation of dolomite dust highly influenced the overall evaluated tensile properties of glass fiber reinforced composites. The increasing dolomite dust content led to a gradual decrease in tensile strength with a simultaneous increase in tensile modulus of the composites.…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%